The contribution of skate blade properties to skating speed - McGurk, M. (2015)
The purpose of the study was to investigate the relative contribution of skate blade properties to on-ice skating speed. Thirty-two male ice hockey players (mean age = 19±2.65 yrs.) representing the Ontario Minor Hockey Association (OMHA; Midget AAA and Junior), Canadian Inter University Sport (CIS: Varsity), Ontario hockey league (OHL) and East Coast Hockey League (ECHL), and the playing positions of forwards (n=18) and defense (n=14) were recruited to participate. Skate related equipment worn by the players for the purpose of the research was documented and revealed that 80% of the players wore Bauer skates, Tuuk blade holders and LS2 skate blades. Subjects completed a battery of eight on-ice skating drills used to measure and compare two aspects of skating speed; acceleration [T1(s)] and total time to complete each drill [TT(s)] while skating on three skate blade conditions. The drills represented skills used in the game of hockey, both in isolation (e.g., forward skating, backward skating, stops and starts, and cornering) and in sequence to simulate the combination of skills used in a shift of game play. The three blade conditions consisted of (i) baseline, represented by the blades worn by the player throughout their current season of play; (ii) experimental blades (EB), represented by brand name experimental blades with manufacturers radius of contour and a standardized radius of hollow; and (iii) customized experimental blades (CEB), represented by the same brand name experimental blades sharpened to the players` preference as identified in the baseline condition. No significant differences were found in acceleration time [T1(s)] or total time to complete [TT(s)] the isolated drills across blade conditions; however significant differences were revealed in both T1(s) and TT(s) measured during the execution of the sequenced drill across blade conditions. A iii Bonferroni post hoc test revealed that players skated significantly faster when skating on the CEB condition compared to the baseline condition (p=.05). A questionnaire assessing subjects perceived comfort, confidence and effort expended while skating on the experimental blades revealed that players were significantly more comfortable when skating on the CEB versus the EB condition (p=.05). Outcomes of the study provide evidence to suggest that the experimental skate blades customized with the players preferred blade sharpening characteristics results in faster skating speed in a combination drill representing skills performed in gameplay.